Technologies of suspension cultivation in bioreactor of the Chlamydophila abortus strain on McCoy cell culture - Yerkin Krykbayev; Nurtas Tyrsynbayev; Nurlan Akhmetsadykov; Damir Khussainov; Zhanat Batanova (Наукові горизонти)
The purpose of the study was to investigate the cultural method of the diagnosis of Chlamydophila abortus. For this purpose, laboratory diagnosis of pathological material from the farm was carried out at the LLP Research and Production Enterprise “Antigen”, where, based on the dThe purpose of the study was to investigate the cultural method of the diagnosis of Chlamydophila abortus. For this purpose, laboratory diagnosis of pathological material from the farm was carried out at the LLP Research and Production Enterprise “Antigen”, where, based on the data of anamnesis, data of occurrence of similar epizootic picture for the last two years, examination and diagnostic manipulations (clinical symptoms, autopsy data, epizootological anamnesis), the preliminary diagnosis “Enzooticata of anamnesis, data of occurrence of similar epizootic picture for the last two years, examination and diagnostic manipulations (clinical symptoms, autopsy data, epizootological anamnesis), the preliminary diagnosis “Enzootic abortion of ewes caused by Chlamydophila abortus” was made. Samples from the organs of aborted foetuses and swabs with vaginal contents were taken to confirm this diagnosis. Complement fixation tests with chlamydia antigen were found to be positive in 7 (23%) of the 30 animals that were examined. To isolate the pathogen, the technology of suspension cultivation in a bioreactor of the Chlamydophila abortus strain on McCoy cell culture was used. Isolated pathological material was grown in McCoy cell cultures that were suspended in a bioreactor in Dulbecco’s Modified Eagle’s Medium (DMEM) nutrient medium with 10% foetal bovine serum and antibiotics at a concentration of 2×105 cells/mL. Enzyme immunoassay was a confirmation of the successful result of cultivation. Enzyme immunoassay confirmed the presence of the pathogen in 60.9% of cases. 25 samples were received, which were positive. Thus, the accuracy of the cultural diagnostic method turned out to be almost 3 times higher than the serological diagnostic method. Serological examination revealed 23% presence of Chlamydophila abortus in the samples, and the cultural diagnostic method revealed 60.9%. Unfortunately, in practice, the use of the cultural diagnostic method is associated with a time-delayed result, which is a disadvantage of this diagnostic method compared to the use of polymerase chain reaction